Advancement in computer vision: Unveiling the spectrum of possibilities - naufal azzam, julian; normalisa (Liaison Journal of Engineering, 2023)
This article provides a comprehensive overview of the rapidly growing field of computer vision, tracing its historical origins, outlining fundamental principles, examining industry applications, addressing ethical challenges, and providing an outlook on future directions. Key topics include image processing techniques, feature extraction, pattern recognition, neural networks, use cases in areas such as healthcare and transportation, bias and privacy considerations, as well as new research in explainable artificial intelligence and multi-modal learning. This analysis outlines how computer vision is transforming human-computer interaction by improving visual perception and understanding while emphasizing the need for responsible and transparent development. Keywords: Computer Vision, Image Processing, Neural Network, Artificial Intelligence, Multi-modal Learning.